IMPLEMENTATION OF UTTP EQUIPMENT CALCULATION AND RECAACING IN LAW ENFORCEMENT IN THE FIELD OF LEGAL METROLOGY IN MAKASSAR CITY - Fachri Muhammad B; Asis, Abd; Mirzana, Hijrah Adhyanti (Awang Long Law Review, 2022)
The purpose of this study was to analyze the implementation of calibration and re-calibration in Makassar City as an effort in law enforcement in the field of legal metrology. The research is empirical-legal research. A research location is a place or area where the author conducts research. In the context of this research, the author conducted research in the city of Makassar, specifically the Regional Technical Implementation Unit for Legal Metrology, Makassar City, Makassar Police Station, and several traders. The reason the author chooses the Makassar City UPTD is that the institution is authorized and competent in providing data regarding the supervision of the implementation of calibration and re-calibration in the city of Makassar. Then at the Makassar City Police, the author will ask for data related to Crime in the Legal Metrology field and some traders to provide information regarding the measuring instruments, measurements, and scales used. The data used are primary data and secondary data. The collected data are then analyzed qualitatively. The results of the study indicate that the authority in the management of legal metrology at the center is carried out by the DITMET of the Ministry of Trade whose task is to carry out the formulation, implementation, and control of policies, drafting guidelines, norms, standards, procedures, and criteria as well as providing technical guidance and evaluation of policy implementation in the field of metrology. legal in order to provide wider space for regions to regulate and manage the lives of their citizens, the central government establishes a regional autonomy policy through Law Number 23 Year 2014 (as was the last amendment through Law Number 9 Year 2015) concerning Regional Government. The transfer of authority for the implementation of the previous calibration and calibration from the provincial government is then transferred to the Regency/City Government, which then each region has the right to form a legal Metrology Unit whose task is to carry out calibration and recalculation. In the case of calibration and recalculation obligations, each UTTP instrument has a period of calibration and recalibration period and the one who is entitled to perform the calibration is the calibrator. As a follow-up to the Regional Government Law, the city of Makassar has established a UML in 2017 through Makassar Mayor Regulation No. 82 Year 2017 concerning the formation, position, organizational structure, duties and functions, and work procedures of the legal metrology technical implementing unit at the trade office.